Molecular diversity underlying cortical excitatory and inhibitory synapse development. (December 2018) - Favuzzi, Emilia; Rico, Beatriz
Highlights: Molecular diversity critically contributes to synapse diversity. Different molecules regulate excitatory and inhibitory synapse development. Synapse type-specific molecules are employed at all steps of synaptic development. The molecular diversity of different inhibitory synapses is unknown. Abstract : The complexity and precision of cortical circuitries is achieved during development due to the exquisite diversity of synapse types that is generated in a highly regulated manner. Here, we review the recent increase in our understanding of how synapse type-specific molecules differentially regulate the development of excitatory and inhibitory synapses. Moreover, several synapse subtype-specific molecules have been shown to control the targeting, formation or maturation of particular subtypes of excitatory synapses. Because inhibitory neurons are extremely diverse, a similar molecular diversity is likely to underlie the development of different inhibitory synapses making it a promising topic for future investigation in the field of the synapse development.